Inquiry-based science education - Gillies, Robyn M., 1949- (Global science education, 2020)
Students often think of science as disconnected pieces of information rather than a narrative that challenges their thinking, requires them to develop evidence-based explanations for the phenomena under investigation, and communicate their ideas in discipline-specific language as to why certain solutions to a problem work. The author provides teachers in primary and junior secondary school with different evidence-based strategies they can use to teach inquiry science in their classrooms. The research and theoretical perspectives that underpin the strategies are discussed as are examples of how different ones areimplemented in science classrooms to affect student engagement and learning. Key Features: Presents processes involved in teaching inquiry-based science Discusses importance of multi-modal representations in teaching inquiry based-science Covers ways to develop scientifically literacy Uses the Structure of Observed learning Outcomes (SOLO) Taxonomy to assess student reasoning, problem-solving and learning Presents ways to promote scientific discourse, including teacher-student interactions, student-student interactions, and meta-cognitive thinking